2019
DOI: 10.3390/ani9060342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Modulation of Selenium Form and Level on Performance, Tissue Retention, Quality of Frozen Stored Meat and Gene Expression of Antioxidant Status in Ross Broiler Chickens

Abstract: This study compares between different selenium forms (sodium selenite; SeS, selenomethionine; Met-Se or nano-Se) and levels on growth performance, Se retention, antioxidative potential of fresh and frozen meat, and genes related to oxidative stress in Ross broilers. Birds (n = 450) were randomly divided into nine experimental groups with five replicates in each and were fed diets supplemented with 0.3, 0.45, and 0.6 mg Se/kg as (SeS, Met-Se), or nano-Se. For overall growth performance, dietary inclusion of Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 74 publications
2
38
0
1
Order By: Relevance
“…For example, nanoselenium has been found to be more effective in improving production performance, meat quality and minimizing oxidative stress in broiler chicken when compared to selenomethionine and inorganic Se. This can result from the efficient retention of this novel delivery form of selenium within body, better utilization, enhanced conversion efficiency and improved antioxidant defense (Ibrahim et al 2019). Similarly, nanoparticles of gold, silver and copper have shown potential roles in improving production performance, antioxidant defense system, and immunological response against diseases.…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%
“…For example, nanoselenium has been found to be more effective in improving production performance, meat quality and minimizing oxidative stress in broiler chicken when compared to selenomethionine and inorganic Se. This can result from the efficient retention of this novel delivery form of selenium within body, better utilization, enhanced conversion efficiency and improved antioxidant defense (Ibrahim et al 2019). Similarly, nanoparticles of gold, silver and copper have shown potential roles in improving production performance, antioxidant defense system, and immunological response against diseases.…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%
“…Also, Yang et al (2012) found that the AST, alkaline phosphatase and urea concentrations were observed to be insignificant when compared between Se supplemented and control group in chicks. On the other hand, Selim et al (2015) and Ibrahim et al (2019) showed that the activity of liver enzymes of Ross broiler chickens including ALT and AST were not significantly affected by the interaction between different sources of Se. In addition, Yang et al (2012) observed that Se (organic or inorganic) didn't affected liver enzymes.…”
Section: Renal and Liver Function Testsmentioning
confidence: 92%
“…Serum bactericidal activity to Aeromonas hydrophila strain was determined according to Rainger and Rowley (1993). Serum lysozyme activity was measured with the turbidimetric method described by Engstad et al (1992) and the results are expressed as one unit of lysozyme activity that defined as a reduction in absorbance at 0.001/min. Lysozyme activity = (A0 -A) / A.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium (Se) is an essential trace element required for numerous physiological functions in animals, ranging from immunoregulatory function 1,2 , reproduction 3 , and protecting the tissue damage by the maintenance of the antioxidant system 4,5 . The mechanisms in which Se functions solely is applied via Se-containing proteins 6 .…”
Section: Introductionmentioning
confidence: 99%